2007
DOI: 10.1261/rna.606407
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of picornavirus replication by the poly(A) tail in a cell-free extract is largely independent of the poly(A) binding protein (PABP)

Abstract: Picornavirus infectivity is dependent on the RNA poly(A) tail, which binds the poly(A) binding protein (PABP). PABP was reported to stimulate viral translation and RNA synthesis. Here, we studied encephalomyocarditis virus (EMCV) and poliovirus (PV) genome expression in Krebs-2 and HeLa cell-free extracts that were drastically depleted of PABP (96%-99%). Although PABP depletion markedly diminished EMCV and PV internal ribosome entry site (IRES)-mediated translation of a polyadenylated luciferase mRNA, it displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 58 publications
5
25
0
Order By: Relevance
“…3B, treatment of the translation reaction mixtures with glutathione S-transferase (GST)-Paip2 but not GST alone inhibited translation of both capped, polyadenylated RNA and PV5Ј-FLuc-3Ј-A 71 but not PV5Ј-FLuc-3Ј-A 0 , which has no poly(A) tail. The degree of inhibition approached 40%, similar to previously reported effects of GST-Paip2 on IRES translation in vitro (32,56). To test the importance of PABP to translation of these reporters, recombinant PABP was added to supplement endogenous PABP in these reactions.…”
Section: C Pro Inhibits Ires-mediated Translation Of Poly(a) ؉ and Psupporting
confidence: 79%
See 1 more Smart Citation
“…3B, treatment of the translation reaction mixtures with glutathione S-transferase (GST)-Paip2 but not GST alone inhibited translation of both capped, polyadenylated RNA and PV5Ј-FLuc-3Ј-A 71 but not PV5Ј-FLuc-3Ј-A 0 , which has no poly(A) tail. The degree of inhibition approached 40%, similar to previously reported effects of GST-Paip2 on IRES translation in vitro (32,56). To test the importance of PABP to translation of these reporters, recombinant PABP was added to supplement endogenous PABP in these reactions.…”
Section: C Pro Inhibits Ires-mediated Translation Of Poly(a) ؉ and Psupporting
confidence: 79%
“…The previously described shutoff mechanisms of cleavage of PTB, PCBP2, binding of PCBP2 to the cloverleaf, and now PABP cleavage are not mutually exclusive and are likely complementary. More recently, PABP was reported to not be required for viral RNA replication in PABP depletion experiments, though depletion did decrease viral IRES translation (56). In other work, we have shown that PABP inhibits 3D pol activity on viral RNA poly(A) templates, which complements these results.…”
supporting
confidence: 86%
“…The potential contribution of PABP bound to poly(A) sequences during the initiation of negative-strand RNA synthesis has been considered previously (21,35). Nevertheless, recent evidence suggests that picornavirus RNA replication does not require PABP (43). For this reason and for simplicity, we chose to exclude PABP from the diagrams in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7B, note 3Ј poly(A) tail lengths of ϳ28 to 43 bases]. The PV A (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) RNA templates were transcribed into 5Ј VPglinked polyU RNA products (Fig. 7C).…”
Section: Vpg-linked Poly(u) From Pv a (84) A (51)mentioning
confidence: 99%
“…3A). First, the IRES element in EMCV recruits the translation initiation complex directly, through interactions with eIF4G, and that process can be stimulated by the poly(A) tail (Humphreys et al 2005) and PABP, the poly(A) binding protein (Bergamini et al 2000;Svitkin et al 2007). Second, in contrast to capped mRNAs, the AUG is positioned at the site of ribosome recruitment, so there is no scanning and AUG recognition occurs in a spatially restricted manner (Kaminski et al 1994).…”
Section: Implications For Mirna-mediated Repression Of Ires-driven Trmentioning
confidence: 99%